Handbook of Intuition Research as Practice 2020
DOI: 10.4337/9781788979757.00033
|View full text |Cite
|
Sign up to set email alerts
|

Intuition: scientific, non-scientific or unscientific?

Abstract: In this chapter we propose expanding the scope of what is covered by scholarly research on intuition. Specifically, we suggest expanding this research into an area often labeled as unscientific. Much of what is considered scientific knowledge today used to be outside the realm of scientific, until someone achieved an understanding of a phenomenon that enabled scientific inquiry. Based on this premise, we argue that what is not scientifically understood about intuition is not unscientific, but non-scientific. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…In other words, it is all about sensing while sensemaking is suspended. (cf Dörfler and Bas, 2020a) Phenomenological psychological reduction, in turn, only requires the researchers (Giorgi, 1997) to suspend their "belief in the existence of what presents itself in the life-world. Instead the focus is on the subjective appearances and meanings" (Finlay, 2008b, p 3).…”
Section: Bracketing Revisitedmentioning
confidence: 99%
“…In other words, it is all about sensing while sensemaking is suspended. (cf Dörfler and Bas, 2020a) Phenomenological psychological reduction, in turn, only requires the researchers (Giorgi, 1997) to suspend their "belief in the existence of what presents itself in the life-world. Instead the focus is on the subjective appearances and meanings" (Finlay, 2008b, p 3).…”
Section: Bracketing Revisitedmentioning
confidence: 99%
“…Drawing on earlier arguments (e.g. Dörfler and Bas, 2020) and findings from psychological experiments, it was concluded that intuitions have a high potential to be valid when they are based on expertise and experience in the research area, build on large sets of input data, and result from immersion in those data. All of this often holds true for researchers' intuitions.…”
Section: Discussionmentioning
confidence: 99%
“…Many aspects of intuition are still contested and underexplored (Baldacchino et al, 2015;Hodgkinson and Sadler-Smith, 2018;Sinclair, 2010). Nevertheless, there is consensus about some of its key features (Dörfler and Ackermann, 2012;Dörfler and Bas, 2020;Dörfler and Stierand, 2017). In contrast with analytical processing, intuitive processing is seen as a rather fast, spontaneous process that does not follow the rules of logic; in contrast with an analytically derived outcome, an intuitive outcome is tacit and holistic, and intuitors feel confident about it, despite lacking evidence.…”
Section: The Concept Of Intuitionmentioning
confidence: 99%
See 2 more Smart Citations